Ferroelectric and ferromagnetic properties of K-doped 0.7BiFeO 3-0.3BaTiO3 multiferroic ceramics - Prasatkhetragarn, A.; Jantaratana, P.; Vittayakorn, N.; Yotburut, B.; Yimnirun, R. (My University, 2013)
Lead-free and multiferroic 0.7BiFeO3-0.3BaTiO3 ceramics doped with K (0.5, 1.0, 3.0 and 5.0 mol%) have been successfully prepared by a solid state mechanical milling technique. The single phase perovskite was found at calcination temperature of 900?C for 6 h. The effects of K doping on the crystal structure, microstructure, magnetic and electrical properties of lead-free 0.7BiFeO3-0.3BaTiO3 ceramics were investigated and discussed. The fracture micrographs of specimens elucidate the grain growth behavior with increasing K content up to 3.0 mol%. The weak ferromagnetic and ferroelectric properties were observed in rhombohedrally- distorted 0.7BiFeO3-0.3BaTiO3 perovskite ceramic. However, the addition of K into 0.7BiFeO3-0.3BaTiO3 has been found to improve the ferroelectric and ferromagnetic properties, with the optimized properties obtained at 3.0 mol% content of K. Copyright © 2013 Taylor & Francis Group, LLC.
Keywords: BF-BT; Ferroelectric; Ferromagnetic; Multiferroic; Potassium-doped